ACL Reconstruction Graft Angle and Outcomes: Transtibial vs Anteromedial Reconstruction. Issue 2 (December 2020) - Stone, Austin V.; Chahla, Jorge; Manderle, Brandon J.; Beletsky, Alexander; Bush-Joseph, Charles A.; Verma, Nikhil N.
Background: The importance of creating an anatomic anterior cruciate ligament (ACL) reconstruction has been receiving significant attention. The best technique by which to achieve this anatomic reconstruction continues to be debated. The two most common methods are the transtibial (TT) and anteromedial (AM) techniques. Each has its advantages and disadvantages, and the literature comparing the two remains uncertain. Questions/Purposes: In this prospective comparative study, we aimed to compare the ACL graft and tunnel angles achieved using the anatomic transtibial (TT) and anteromedial (AM) techniques; compare the ACL graft and tunnel angles in knees that have undergone ACL reconstruction and knees with intact ACLs; and determine whether differences in the graft or tunnel angle produce differences in clinical outcomes, as measured using both physical exam and patient-reported outcomes, after ACL reconstruction. Methods: Patients who underwent primary ACL reconstruction with bone–tendon–bone grafts using a TT or AM technique were included. Femoral graft angle (FGA), tibial graft angle (TGA), and sagittal orientation of the reconstructed ACL and contralateral native ACL were measured on post-operative magnetic resonance imaging. Post-operatively, patients underwent measurement of knee stability and completed the Knee Injury and Osteoarthritis Outcome Score (KOOS) survey. Results: Twenty-nine patients were enrolled (AM group, 14; TT group, 15); at follow-up, KOOS data were available for 26 patients (13 in each group). There were no differences in sagittal ACL graft angle between groups or in comparison with the normal knee. The FGA was more vertical after TT reconstructions; the TGA was comparable between groups. There were no significant differences in 2-year post-operative physical exam measurements or in KOOS scores. Conclusion: Anatomic ACL angle was restored after reconstruction with both the TT and AM techniques, despite different FGAs. No significant differences in clinical outcome were noted between groups on physical exam or KOOS at 2 years after surgery. These results suggest that TT reconstruction results in a graft position similar to that seen in AM reconstruction and that the location of the intra-articular tunnel aperture matters more than the orientation of the tunnel.